The Nature of Managerial Work: A Book Review of Mintzberg - Willson Gustiawan (Politeknik Negeri Padang, 2019)
The purpose of this paper is to review an old holy book of management: the nature of managerial work’s Mintzberg which originally published since 1973. The book is the answer of the young Mintzberg on what was his father do at the office. Mintzberg then details the kind of managers’ activities, managerial work characteristics, managerial basic role, managerial jobs variations, and management science. Briefly, the aim of the book is to develop a manager job description through management science approach. This book review paper emphasizes the last chapter as integrated basic research findings in three previous chapters. In literature review, there is explanation about the outline of the analysis that how theory is developed. The implication for stakeholders around manager and future work as discussed. Keywords: managerial work, Mintzberg, development of theory